Productivity and nutrient removal by the microalga Chlamydopodium fusiforme grown outdoors in BG-11 and piggery wastewater - Zittelli, Graziella Chini; Silva Benavides, Ana Margarita; Silovic, Tina; Ranglová, Karolína; Masojídek, Jiří; Cicchi, Bernardo; Faraloni, Cecilia; Touloupakis, Eleftherios; Torzillo, Giuseppe (Frontiers in Marine Science, 2022)
The objective of this work was to test the growth of the freshwater microalga Chlamydopodium fusiforme MACC-430 in diluted piggery wastewater (PWW) for biomass production which is a potential producer of biostimulating and antimicrobial compounds. The productivity and effectiveness in removing nitrogen and phosphorus by the cultures were tested outdoors in open ponds by comparing the mineral medium BG-11 medium (control) and piggery wastewater (PWW). Daily biomass yields were found 14.7 ± 4.6g m-2 d-1 in BG-11 and 17.6 ± 6.7g m-2 d-1 in 10-fold diluted wastewater (PWW10) with deionized water. Further increase in the biomass productivity yield (33.1 ± 5.6g m-2 d-1) was achieved with more concentrated PWW (5-fold dilution – PWW5). Nitrogen removal rate (N-NH4+) reached 21.4 ± 2.9mg L-1 d-1 in cultures grown in PWW10 and increased to 38.4±16.3mg L-1 d-1 using the PWW5. The use of undiluted PWW strongly increased the bacterial load, which caused the loss of the culture. The photosynthetic performance measured as the maximum fluorescence yield Fv/Fm ratio in both the PWW10 and BG-11 cultures showed a cyclic behavior, as it decreased during the day and recovered at night. However, in the cultures grown in diluted PWW the Fv/Fm ratio slightly increased throughout the cultivation. Between PWW10 and BG-11, no significant differences were observed in photosynthetic oxygen evolution; on the contrary, PWW5 showed a 30% reduction compared to PWW10 and BG-11. Significantly lower chlorophyll and carotenoid contents were found in the cultures grown in PWW compared to BG-11. Biochemical composition showed a slightly higher protein content in biomass grown in PWW10 (53.4%) compared to BG-11 (52.7%). The protein content further increased (61.3%) when the more concentrated PWW5 was used. The biomass, particularly that produced on PWW, revealed antimicrobial activity against plant pathogens, including fungi, and oomycete, while rather weak biostimulant activity was determined for the C. fusiforme biomass independently of the cultivation medium. Results demonstrated that C. fusiforme is a robust strain suitable to be grown in diluted PWW outdoors with a high nutrient removal rate.